Using efficient bimetallic FeCo-ZIFs catalyst for Ciprofloxacin degradation in the presence of potassium peroxydisulfate - Dang Hoang An Cao; Thu Le; Thi Truong An Pham; My Tien Ha; Thi Kim Ngan Nguyen; Luu Ngoc Hanh Cao; Huynh Giao Dang (CTU Journal of Innovation and Sustainable Development)
Solvothermal synthesis was used for the successful manufacture FeCo-ZIFs bimetallic materials. The materials' properties were determined using a variety of techniques, including Fourier-transform infrared spectroscopy (FT-IR), energy dispersive X-ray spectroscopy (EDX), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and nitrogen adsorption ability. The obtained FeCo-ZIFs were acted as catalysts to remove Ciprofloxacin in aqueous media with high efficiency. It showed that the decomposition efficiency of Ciprofloxacin reached 92.1% with a weight of 0.4 g/L FeCo-ZIFs, and 0.3 g/L potassium peroxydisulfate for 30 min at room temperature (30±2oC). According to research, this is the first time FeCo-ZIFs was applied to treat Ciprofloxacin.